Vaginal Vault Dehiscence and Increased Use of Vaginal Vault Brachytherapy: What are the Implications?. Issue 9 (1st November 2012) - Wiebe, Ericka; Covens, Allan; Thomas, Gillian
Abstract : Abstract: Literature reports describe the potential for increased incidence of vaginal vault dehiscence after minimally invasive surgery, and incidental reports of vaginal vault dehiscence with vaginal vault brachytherapy. This review explores the risk of increased vaginal complications in a setting of greater use of both minimally invasive surgical techniques and adjuvant vaginal vault brachytherapy in early endometrial cancer. The impact of associated patient-related and tumor-related risk factors on clinical decision making is evaluated in selecting therapy that provides optimal tumor control while minimizing treatment adverse effects.